Sanctuary : Ambush - Book 1 - Coble, Colleen (Nashville, Tennessee : Thomas Nelson, 2025)
"She'll do anything to uncover the truth of her parents' murder--even work alongside the man who once broke her heart"--
Keywords: Wildlife refuges -- Fiction; Women veterinarians -- Fiction; Homecoming -- Fiction; Parents -- Fiction. -- Death; Murder -- Fiction. -- Investigation; Man-woman relationships -- Fiction; Alabama -- Fiction; Christian fiction; Thrillers (Fiction); Romance fiction; Novels